Blood-pressure variability in patients with obstructive sleep apnea: current perspectives - Marrone O (Dove Medical Press, 2018)
Oreste Marrone,1 Maria R Bonsignore1,2 1National Research Council of Italy, Institute of Biomedicine and Molecular Immunology, 2DiBiMIS, University of Palermo, Palermo, Italy Abstract: Obstructive sleep apnea (OSA) is often associated with hypertension and other cardiovascular diseases. Blood pressure (BP) variability is part of the assessment of cardiovascular risk. In OSA, BP variability has been studied mainly as very short-term (beat-by-beat) and short-term (24-hour BP profile) variability. BP measured on consecutive heartbeats has been demonstrated to be highly variable, due to repeated peaks during sleep, so that an accurate assessment of nocturnal BP levels in OSA may require peculiar methodologies. In 24-hour recordings, BP frequently features a “nondipping” profile, ie, <10% fall from day to night, which may increase cardiovascular risk and occurrence of major cardiovascular events in the nocturnal hours. Also, BP tends to show a large “morning BP surge”, a still controversial negative prognostic sign. Increased very short-term BP variability, high morning BP, and nondipping BP profile appear related to the severity of OSA. Treatment of OSA slightly reduces mean 24-hour BP levels and nocturnal beat-by-beat BP variability by abolishing nocturnal BP peaks. In some patients OSA treatment turns a nondipping into a dipping BP profile. Treatment of arterial hypertension in OSA usually requires both antihypertensive pharmacological therapy and treatment of apnea. Addressing BP variability could help improve the management of OSA and reduce cardiovascular risk. Possibly, drug administration at an appropriate time would ensure a dipping-BP profile. Keywords: sleep apnea, ambulatory blood-pressure monitoring, beat-by-beat measurements, blood-pressure dipping, morning blood-pressure surge